William R. McIntyre : paladin of the common law - McConnell, W. H. (William Howard), 1930- (Published for Carleton University by McGill-Queen's University Press, 2000)
"Using archival resources, interviews with contemporaries, and legal sources, W.H. McConnell traces McIntyre's personal evolution from defending the Charter as a workable counterpoint to established common law principles to gradual disenchantment with its overuse, by many of his colleagues and the lower courts, for developing social policy. In retrospect McIntyre's reservations have been prophetic: the "interventionist" trend has given rise to considerable criticism of the court by legal professionals, the media, and the Canadian public. He remained, however, a staunch proponent of freedom of expression and, in the Andrews case, framed the pivotal definition of "equality rights" in section 15 of the Charter that is still prevalently applied in Canadian courts."--Jacket